Pentoxifylline Sensitizes Cisplatin-Resistant Human Cervical Cancer Cells to Cisplatin Treatment: Involvement of Mitochondrial and NF-Kappa B Pathways - Bravo-Cuellar, Alejandro; Ortiz-Lazareno, Pablo Cesar; Sierra-Díaz, Erick; Solorzano-Ibarra, Fabiola; Méndez-Clemente, Anibal Samael; Aguilar-Lemarroy, Adriana; Jave-Suárez, Luis Felipe; Ruiz Velazco-Niño, Édgar; Hernández-Flores, Georgina (Frontiers in Oncology, 2020)
Background: Cervical cancer continues to be a major public health problem worldwide, and Cisplatin is used as first-line chemotherapy for this cancer; however, malignant cells exposed to CISplatin (CIS) become insensitive to the effects of this drug. PenToXifylline (PTX) is a xanthine that sensitizes several types of tumor cells to apoptosis induced by antitumor drugs, such as Adriamycin, Carboplatin, and CIS. The effects of PTX on tumor cells have been related to the disruption of the NF-kappaB pathway, thus preventing the activation of cell survival mechanisms such as the expression of anti-apoptotic genes, the secretion of proinflammatory interleukins, and growth factors. Objective: In this work, we studied the antitumor proprieties of PTX in human SiHa cervical carcinoma cells resistant to CIS. Materials and Methods: SiHa and HeLa cervical cancer cells and their CIS-resistant derived cell lines (SiHaCIS-R and HeLaCIS-R, respectively) were used as in-vitro models. We studied the effects of PTX alone or in combination with CIS on cell viability, apoptosis, caspase-3, caspase-8, and caspase-9 activity, cleaved PARP-1, anti-apoptotic protein (Bcl-2 and Bcl-xL) levels, p65 phosphorylation, cadmium chloride (CdCl2) sensitivity, Platinum (Pt) accumulation, and glutathione (GSH) levels, as well as on the gene expression of GSH and drug transporters (influx and efflux). Results: PTX sensitized SiHaCIS-R cells to the effects of CIS by inducing apoptosis, caspase activation, and PARP-1 cleavage. PTX treatment also decreased p65 phosphorylation, increased Pt levels, depleted GSH, and downregulated the expression of the ATP7A, ATP7B, GSR, and MGST1 genes. Conclusion: PTX reverses the acquired phenotype of CIS resistance close to the sensitivity of parental SiHa cells.